2019
DOI: 10.1210/endocr/bqz033
|View full text |Cite
|
Sign up to set email alerts
|

Oviductal Retention of Embryos in Female Mice Lacking Estrogen Receptor α in the Isthmus and the Uterus

Abstract: Estrogen receptor α (ESR1; encoded by Esr1) is a crucial nuclear transcription factor for female reproduction and is expressed throughout the female reproductive tract. To assess the function of ESR1 in reproductive tissues without confounding effects from a potential developmental defect arising from global deletion of ESR1, we generated a mouse model in which Esr1 was specifically ablated during postnatal development. To accomplish this, a progesterone receptor Cre line (PgrCre) was bred with Esr1f/f mice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
3
6
0
Order By: Relevance
“…The retention of preimplantation embryos in the oviduct established as a significant contributor to implantation failures, presenting challenges to the overall reproductive health of women [4][5][6]. Embryo transport in the oviduct is known to be controlled primarily by two major physiological responses: ciliary activity and muscle contractility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retention of preimplantation embryos in the oviduct established as a significant contributor to implantation failures, presenting challenges to the overall reproductive health of women [4][5][6]. Embryo transport in the oviduct is known to be controlled primarily by two major physiological responses: ciliary activity and muscle contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Any perturbations in these early pregnancy events can lead to adverse ripple effects that can compromise pregnancy outcomes. Previous studies have reported that impaired oviductal transport of embryos can lead to pregnancy failure and cause infertility in mice [3][4][5][6]. However, the underlying mechanism is not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al emphasized that the different levels of GnRH were among the reasons for the different number of lambs [ 44 ]. During the estrous cycle, estrogen and progesterone affect the morphological and functional responses of the oviduct, which are critical for female fertility [ 39 , 45 ]. In the present study, most DEGs in the LL and LH comparison groups were significantly enriched in pathways, including GnRH, thyroid hormone, prolactin signaling pathway, dopaminergic synapse, insulin secretion, melanogenesis, and progesterone-mediated oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…All mentioned processes are controlled by sex hormones, nerves, growth factors, and other paracrine signals [11]. Sufficient expression of estrogen receptor alpha in the isthmus of the oviduct and normal progesterone levels allow for the successful transport of the embryo from the Fallopian tube to the uterus [12].…”
Section: Introductionmentioning
confidence: 99%